2021
DOI: 10.3390/cancers13081984
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast MMP14-Dependent Collagen Processing Is Necessary for Melanoma Growth

Abstract: Skin homeostasis results from balanced synthesis and degradation of the extracellular matrix in the dermis. Deletion of the proteolytic enzyme MMP14 in dermal fibroblasts (MMP14Sf−/−) leads to a fibrotic skin phenotype with the accumulation of collagen type I, resulting from impaired proteolysis. Here, we show that melanoma growth in these mouse fibrotic dermal samples was decreased, paralleled by reduced tumor cell proliferation and vessel density. Using atomic force microscopy, we found increased peritumoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 57 publications
2
17
1
Order By: Relevance
“…It is increasingly clear that in vitro macrophage polarization protocols do not re-capitulate the complex macrophage phenotypes observed in vivo [ 45 , 46 ]. Single-cell approaches have provided a more complete look into macrophage heterogeneity in tumor infiltrates [ 47 , 48 ], with surrounding cells and cues that influence their behavior and shape their functional response [ 12 , 49 , 50 ]. Developing experimental models to study TAMs in vitro is not as simple as inducing a cell program through a signaling pathway, especially when the definition of polarization state, such as the M2-like profile, has expanded over the years to fit the pathophysiology of the macrophages [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly clear that in vitro macrophage polarization protocols do not re-capitulate the complex macrophage phenotypes observed in vivo [ 45 , 46 ]. Single-cell approaches have provided a more complete look into macrophage heterogeneity in tumor infiltrates [ 47 , 48 ], with surrounding cells and cues that influence their behavior and shape their functional response [ 12 , 49 , 50 ]. Developing experimental models to study TAMs in vitro is not as simple as inducing a cell program through a signaling pathway, especially when the definition of polarization state, such as the M2-like profile, has expanded over the years to fit the pathophysiology of the macrophages [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive deposition of extracellular matrix, with enhanced collagen accumulation, is linked to the growth of many cancers [24][25][26], although the influence of collagen is diverse on the different types of cancers. Mice lacking MMP14 in stromal fibroblasts (MMP14 Sf−/− ) display skin fibrosis and reduced melanoma growth due to enhanced collagen I accumulation and increased skin stiffness [13,14]. However, it was unclear whether additional extracellular matrix alterations due to MMP14 deletion in fibroblasts, the primary producer of extracellular matrix in tissues, contribute to the observed effect.…”
Section: Negative Effect Of Mmp14 Sf−/− Fibroblast Matrix On Melanoma Proliferation and Migrationmentioning
confidence: 99%
“…Indeed, MMP14 deletion in fibroblasts led to the development of a fibrosis-like skin phenotype [13]. Dermal alterations, collagen I accumulation, and increased tissue stiffness also restrained melanoma growth [14]. In addition to collagen I, likely other collagens were altered around these tumors, as increased hydroxyproline would result from all types of collagens [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that MMP14 is involved in the progression of cervical cancer (CC) by promoting angiogenesis, invasion, and lymph node metastasis, and it has also been reported that MMP14 overexpression is associated with poor prognosis of cervical cancer (7)(8)(9). At the same time, a large number of studies have shown that MMP14 is closely related to the invasion, migration, and angiogenesis of ovarian cancer (10), gastric cancer (11), glioma (12), pancreatic cancer (12), hepatocellular carcinoma (13), colon cancer (14), and melanoma (15). However, there has been no study on the effect of MMP14 on the immune infiltration and prognosis of pan tumor cells, which needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%